Can behavioural science be used to understand factors that influence the prescription choice for Parkinson’s disease? A pan-European focus group study of clinicians’ prescribing practice - Emma Begley; Jason Michael Thomas; William Hind; Carl Senior (BMJ Open)
Objectives This study aimed to establish a consensus on key factors that influence medication choices for Parkinson’s disease and to identify the behavioural determinants of these factors using behavioural change theory as a theoretical lens.Design This qualitative study used the nominal group technique to conduct structured online focus group meetings. A facilitator guided participants to (1) individually generate a list of factors that influence their decision to prescribe, (2) collectively share these factors, (3) refine and clarify factors and (4) rank the most important factors. Subsequently, the most important factors identified were mapped to the Theoretical Domains Framework (TDF) and the Capability, Opportunity, Motivation–Behaviour (COM-B) model to identify the behavioural determinants that influence medication choice.Participants Eighteen healthcare professionals, including neurologists, consultants and specialist nurses/practitioners who prescribe medication, were recruited across Europe and participated in one of seven focus groups.Results There was good consensus among the participants about which factors influence their prescribing decisions. Overall, participants identified 60 unique factors that were broadly categorised into the following themes: medical or symptom concern, patient characteristics, side effects, access to treatment, clinical guidelines, social support and patient preference. Factors discussed and prioritised by the participants aligned with seven of the 14 TDF domains: knowledge; memory, attention and decision processes; beliefs about consequences; goals; social/professional role and identity; environment context and resources; and social influences. Together, these were subsequently mapped onto four of the six subdomains of the COM-B model: psychological capability, reflective motivation, physical opportunity and social opportunity.Conclusions These findings suggest that prescribing decisions for Parkinson’s disease are determined by a complex range of factors linked to the COM-B components capability, motivation and opportunity. These can be further understood by specific behavioural domains, as identified by the TDF, which should be targeted to help optimise subsequent prescribing decisions.